Effects of Atopic Dermatitis and Gender on Sebum Lipid Mediator and Fatty Acid Profiles - Agrawal, Karan (Prostaglandins Leukot Essent Fatty Acids, 2018)
Skin disease alters cutaneous lipid mediator metabolism, and if skin secretions contain evidence of these changes, they may constitute useful clinical matrices with low associated subject burden. The influences of skin diseases on sebum lipid mediators are understudied. Here, sebum oxylipins, endocannabinoids, sphingolipids, and fatty acids were quantified from the non-lesional bilateral cheeks of subjects with and without quiescent atopic dermatitis (AD) using LC-MS/MS and GC-MS. AD decreased C36 [NS] and [NdS] ceramide concentrations. Compared to males, females demonstrated increased concentrations of oxylipin alcohols and ketones, and saturated and monounsaturated non-esterified fatty acids, as well as decreased concentrations of C42 [NS] and [NdS] ceramides. Additionally, contemporaneously collected sweat lipid mediator profiles were distinct, with sebum showing higher concentrations of most targets, but fewer highly polar lipids. Therefore, AD and gender appear to alter sebum lipid metabolism even in non-lesional skin of quiescent subjects.